2004
DOI: 10.1016/s0264-410x(04)00519-5
|View full text |Cite
|
Sign up to set email alerts
|

Is influenza vaccination cost effective for healthy people between ages 65 and 74 years?A randomised controlled trial

Abstract: The aim of this study was to determine the cost effectiveness of influenza vaccination for healthy people aged 65-74 years living in the UK. People without risk factors for influenza (chronic heart, lung or renal disease, diabetic, immunosuppressed or those living in an institution) were identified from 20 general practitioner (GP) practices in Liverpool in September 1999. 729/5875 (12.4%) eligible individuals were recruited and randomised to receive either influenza vaccine or placebo (ratio 3:1), with all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…On the other hand, studies in the United States have shown the cost-effectiveness or cost-benefits of the influenza vaccine for people with different levels of health risk [3,8,10,11,20,21]. Cost-benefit and cost-effectiveness studies from other countries, including Canada [22], England and Wales, France, Germany [23], The Netherlands [24], New Zealand [25], and some local areas in Taiwan [26], also suggest that vaccinating the elderly is cost-effective and frequently cost saving, although a few have not [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies in the United States have shown the cost-effectiveness or cost-benefits of the influenza vaccine for people with different levels of health risk [3,8,10,11,20,21]. Cost-benefit and cost-effectiveness studies from other countries, including Canada [22], England and Wales, France, Germany [23], The Netherlands [24], New Zealand [25], and some local areas in Taiwan [26], also suggest that vaccinating the elderly is cost-effective and frequently cost saving, although a few have not [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…60,61 The efficacy was found in specific elderly populations (i.e., older patients suffering from frailty, institutionalized elderly subjects, diabetes, chronic heart and chronic pulmonary disease, patients' undergoing haemodialysis and nursing home residents). 62,63 A recent Cochrane review showed the numerous biases of cohort studies that embellished the efficacy of vaccines, with the conclusion that new RCTs were needed.…”
Section: Influenza Vaccinationmentioning
confidence: 99%
“…The prescribing that fell within scope of the QOF was measured in the current study, but other studies have shown that such prescribing is only cost-effective in certain circumstances. As an example: clopidogrel was not cost-effective when compared with aspirin in patients with myocardial infarction; 15 aspirin may have no place in primary prevention; 16 guidance from the National Institute for Health and Clinical Excellence does not recommend beta blockers for anxiety because of evidence for lack of efficacy; 17 the British National Formulary does not recommend clonidine for migraine because of its side-effect profile; 18 influenza vaccination is not costeffective in patients who are healthy; 19 and statins are only cost-effective in primary prevention when used for high-risk patients 20 and those who are low risk may get no benefit at all. 21 Assuming that there is an appropriate rate of prescribing of QOF drugs outside of QOF indications by each practice, this should not alter the slope of the cost-quality relationship.…”
Section: Strengths and Limitationsmentioning
confidence: 99%